Wound Penetration of Cefazolin, Ciprofloxacin, Piperacillin, Tazobactam, and Vancomycin During Negative Pressure Wound Therapy - Rowan, Matthew P. (Adv Wound Care (New Rochelle), 2017)
Objective: Negative pressure wound therapy (NPWT) uses subatmospheric pressure as a noninvasive adjunct to treat wounds and has demonstrated clinical efficacy by accelerating healing of a variety of acute and chronic wounds. NPWT may also play a role in preventing or treating wound infections, possibly by increasing wound penetration of antibiotics. However, clinical data in patients undergoing antibiotic and NPWT treatment are limited. Approach: To evaluate the wound penetration of antibiotics in NPWT patients, we conducted a prospective, observational study of burn and trauma patients treated with NPWT and systemic antibiotics. We evaluated the plasma pharmacokinetic profile of systemic vancomycin, ciprofloxacin, cefazolin, and piperacillin/tazobactam, as well as total and unbound antibiotic concentrations in wound exudate from the same patients. Results: Data from 32 patients with 37 wounds undergoing NPWT demonstrated that vancomycin, ciprofloxacin, and piperacillin/tazobactam all penetrated wounds with exudate to plasma concentration ratios more than 0.8. Cefazolin did not penetrate wounds in patients undergoing NPWT as effectively, with an average exudate to plasma concentration ratio of 0.51. Innovation: Clinical data on the wound penetration of antibiotics in patients undergoing NPWT are limited, but these data suggest that antibiotics have different capacities for wound penetration during NPWT that should be considered when making clinical decisions. Conclusion: This initial report suggests that (1) vancomycin, ciprofloxacin, and piperacillin/tazobactam effectively penetrate wounds during NPWT and (2) cefazolin as well as other antibiotics may not penetrate wounds during NPWT.